Design, synthesis and SAR exploration of tri-substituted 1,2,4-triazoles as inhibitors of the annexin A2–S100A10 protein interaction - Reddy, Tummala R.K.; Li, Chan; Guo, Xiaoxia; Fischer, Peter M.; Dekker, Lodewijk V. (Elsevier, 2014)
Recent target validation studies have shown that inhibition of the protein interaction between annexin A2 and the S100A10 protein may have potential therapeutic benefits in cancer. Virtual screening identified certain 3,4,5-trisubstituted 4H-1,2,4-triazoles as moderately potent inhibitors of this interaction. A series of analogues were synthesized based on the 1,2,4-triazole scaffold and were evaluated for inhibition of the annexin A2–S100A10 protein interaction in competitive binding assays. 2-[(5-{[(4,6-Dimethylpyrimidin-2-yl)sulfanyl]methyl}-4-(furan-2-ylmethyl)-4H-1,2,4-triazol-3-yl)sulfanyl]-N-[4-(propan-2-yl)phenyl]acetamide (36) showed improved potency and was shown to disrupt the native complex between annexin A2 and S100A10.